Case 3724: Metochus abbreviatus Scott, 1874 (Insecta, Heteroptera): proposed precedence over Rhyparochromus erosus Walker, 1872 (currently Metochus erosus) - Rédei, Dávid; Kondorosy, Előd; Ishikawa, Tadashi; Aukema, Berend; Brailovsky, Harry; Carapezza, Attilio; Deckert, Jürgen; Dellapé, Pablo; Gao, Cuiqing; Henry, Thomas J; Jung, Sunghoon; Kment, Petr; et al. (Bulletin of Zoological Nomenclature, 2017)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the widely used specific name Metochus abbreviatus Scott, 1874, for a species of rhyparochromid bugs from East Asia. The name is threatened by the senior subjective synonym Rhyparochromus erosus Walker, 1872, which has seldom been used since its first publication. Therefore, precedence of the name Metochus abbreviatus Scott, 1874 over Rhyparochromus erosus Walker, 1872 is proposed.
Keywords: Nomenclature; taxonomy; Heteroptera; Rhyparochromidae; Metochus; East Asia; Metochus abbreviatus; Metochus erosus